A simplified analytical approach for concrete sensible thermal energy storages simulation. (April 2019) - Doretti, Luca; Martelletto, Francesca; Mancin, Simone
Highlights: A simple and easy-to-use lumped capacitance based computing model is presented. The model is compared against experimental data relative to two different concrete TES prototypes. The developed code exhibits an excellent agreement with the experimental data combined to very low computational efforts. A new modified thermal efficiency is developed to compare the concrete thermal energy storage capabilities. Abstract: A simple lumped capacitance based computing model was developed and here presented. The code permits the thermal and energetic analysis of concrete thermal energy storages (TESs) during time. The simulated system consists of a parallelepiped concrete module that can be heated (charging phase) and cooled (discharging phase) by a single-phase working fluid flowing in a tube embedded in the concrete. The modules can be piled up in different configurations to build any desired TES. The new simulation code was validated against the experimental data carried out by ENEA with two different concrete mixtures, during both the heating and cooling processes using mineral oil as working fluid. Furthermore, on the basis of the energetic analysis, two different TES thermal efficiencies were proposed to evaluate the charge or discharge progresses over time. This simple and easy-to-use model allows for a drastic reduction of the computational time needed to simulate the TES and it can be easily integrated, in various arrangements, to any concentrated solar power plant (CSP) and associated energy conversion plant simulation models to have a quick evaluation of the whole system performance.